The Athenian Democracy - Chiara Lasagni (Journal of Interdisciplinary History of Ideas)
The article analyses the manner in which Athenian democracy is frequently employed in contemporary critiques of representative democracy, particularly in response to its perceived crisis. Athenian democracy, with its emphasis on direct citizen participation and the practice of lottery-based selection, is often idealised as an innovative and counter-democratic model, offering alternatives to modern systems shaped by economic monopolies and global information networks. Ancient historians play a pivotal role in this discourse, not merely as observers but as active participants, tasked with providing historically informed insights to enhance public understanding. A significant aspect of this discourse is the reception of Athenian democracy, which has undergone significant evolution over centuries, adapting to meet the shifting needs of political ideologies and discourses. The article challenges the mythologisation of iconic symbols such as Pericles’ Funeral Oration and the kleroterion, emphasising the importance of contextualising these within their true historical settings. This demythologising approach demonstrates the complexities underlying the use of these figures and symbols as simplistic models for contemporary democratic ideals. The concluding section of the article proposes a multifaceted perspective on Athenian democracy. Rather than a static or idealised system, Athenian democracy is better understood as a historically evolving process, comprising complex structures, procedures, and networks of social groupings that facilitated democratic engagement. It is in these elements – multiple, intersecting groups enabling collective governance – that Athenian democracy holds potential lessons for modern political systems.